Identification of Health Needs in Ukrainian Refugees Seen in a Primary Care Facility in Tenerife, Spain - Willian-Jesús Martín-Dorta; Cristo-Manuel Marrero-González; Eva-Lourdes Díaz-Hernández; Pedro-Ruymán Brito-Brito; Domingo-Ángel Fernández-Gutiérrez; Oxana-Migalievna Rebryk-De Colichón; Ana-Isabel Martín-García; Estrella Pavés-Lorenzo; María-Candelaria Rodríguez-Santos; Juan-Francisco García-Cabrera; Janet Núnez-Marrero; Alfonso-Miguel García-Hernández (Nursing Reports)
Background: Ukrainian refugees fleeing the conflict between Russia and Ukraine may face significant challenges to their physical, psycho-emotional, social, and spiritual wellbeing. Aim: To identify the health needs of Ukrainian refugees seen in primary care facilities in Tenerife, Canary Islands, Spain. Methods: A mixed-methods design was employed. Quantitative data were obtained through a descriptive analysis of health records, while qualitative data were collected via focus group interviews and thematic analysis of testimonies. Results: The sample comprised 59 individuals (45.4% of all patients seen). Eight participants from five family groups took part in the focus group. The typical profile of a Ukrainian refugee in the Canary Islands is female (79.7%), relatively young, with a high socio-cultural background, generally in good health, travelling alone or with her minor children. The main reasons for consultation were routine health check-ups and control blood tests. The NANDA-I nursing diagnoses indicated a need for psycho-emotional care, with the most prevalent being Risk for Relocation Stress Syndrome (27.1%); Interrupted Family Processes, Disturbed sleep pattern, Risk for Impaired Resilience (13.6% each); and Anxiety (11.9%). Participants rated the healthcare system positively, but language barriers and long waiting times for access to specific services were noted as limitations. The primary social demands include seeking employment, learning the language, and increasing support groups among Ukrainians themselves. Conclusions: This study underscores the need for a tailored approach to refugee care, considering their unique circumstances and needs. Early provision of information about available healthcare services and protocols can facilitate access, manage expectations, and aid decision-making.